Булінг та його прояви в освітньому середовищі початкової школи - Греба Ілдіко; Greba Ildikó; Гаврилюк Ілона; Gávriljuk Ilona (Видавництво «Код», 2023)
Резюме. Дана стаття спрямована на аналіз та висвітлення важливого аспекту соціальних взаємин серед учнів початкових класів – явища булінгу. Поняття булінгу, яке включає в себе повторювану агресивну поведінку, спрямовану на заподіяння моральної або матеріальної шкоди іншій особі, є поширеним явищем у всьому світі і актуальним у закладах освіти України. Це явище має вплив на всіх учасників освітнього процесу, включаючи як дітей, так і дорослих. Агресія серед дітей та підлітків – явище не нове. Воно набуває різних форм, і, водночас, ми спостерігаємо зниження віку осіб, які проявляють агресивну поведінку.

Abstract. This article is aimed at analysing and highlighting an important aspect of social relations among primary school pupils – the phenomenon of bullying. The concept of bullying, which includes repeated aggressive behaviour aimed at causing moral or material harm to another person, is a widespread phenomenon around the world and is relevant in educational institutions in Ukraine. This phenomenon affects all participants in the educational process, including both children and adults. Aggression among children and adolescents is not a new phenomenon. It takes different forms, and, at the same time, a decrease in the age of those who display aggressive behaviour is observed. Bullying has many causes that can be found in the family, among peers and in the mass media. The paper provides a theoretical analysis of the causes of school violence. The concepts of aggression and bullying, their characteristics and features are considered. The main types of bullying and the signs that define bullying as a form of violence are identified. The factors that lead to the emergence and spread of bullying in educational institutions are investigated. The structure of bullying is studied and its participants are described. Cases and strategies for preventing and counteracting bullying in educational institutions are considered.
Bullying and its manifestations in the educational environment of primary school
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00011820
https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-5
Keywords: агресія; булер; булінг; жертва; освітнє середовище; спостерігач; цькування